Economic forecasts and fiscal policy in the recently acceded member states - Keereman, Filip. (European Economy. Economic papers, 2005)
Forecast errors are large in the recently acceded Member States and the mistakes have a similar order of magnitude in the Commission services' forecasts, Consensus forecasts and projections made by national authorities. The prediction mistakes cannot be attributed to bias or autocorrelation. Volatility in the economic developments and data revisions creating uncertainty on the state of the economy appear the main explanation for the difficulty to make good forecasts. Prediction mistakes for GDP growth lead to wrong projections for general government balances through the operation of the automatic stabilisers, but errors in the discretionary part of the government balance are the largest source of fiscal forecast mistakes. Growth forecast errors influence fiscal policy decisions.